IoT and Blockchain in Supply Chain Management for Advancing Sustainability and Operational Optimization - S. Shyni Carmel Mary; Kishore Kunal; Madeshwaren, Vairavel (International Journal of Computational and Experimental Science and Engineering, 2025)
The rapid advancement of IoT technologies has emerged as a key driver of sustainable development, reshaping industries and societal structures. This study critically examines the intersection of IoT and sustainability by analyzing contemporary literature on the subject. A comprehensive review of IoT-driven innovations highlights their transformative impact across sectors such as agriculture, smart cities, and resource management. The research investigates how digitalization, particularly within supply chains, redefines operational strategies and enhances sustainability metrics. With the integration of technologies like RFID, blockchain, and IoT under Industry 4.0, organizations are revolutionizing process efficiency, transparency, and environmental responsibility. To assess these implications, the study conducts two comparative simulation experiments involving a three-party supply chain in cheese production—one utilizing traditional methods and the other leveraging IoT-based innovations. Results reveal significant improvements in order management efficiency and compliance handling, underscoring the critical role of emerging technologies in fostering sustainable practices. The proposed framework provides valuable insights into the broader management implications of IoT adoption, reinforcing its potential as a catalyst for global sustainability initiatives.